Analysis of Suprapubic and Transrectal Measurements in Assessment of Prostate Dimensions and Volume: Is Transrectal Ultrasonography Really Necessary for Prostate Measurements? - Ozden, Eriz; Gogus, Cagatay; Kilic, Ozcan; Yaman, Onder; Ozdiler, Erol (Urology Journal, 2009)
Introduction: The objective of this study was to evaluate the correlation of suprapubic ultrasonography and transrectal ultrasonography in measurements of prostate dimension and volume. Materials and Methods: One hundred consecutive patients with lower urinary tract symptoms were examined by suprapubic and transrectal ultrasonography modalities in a same session. Measurements of the 3 dimensions of the prostate (anteroposterior, transverse, and craniocaudal) and its volume performed by suprapubic ultrasonography were compared with the corresponding measurements by transrectal ultrasonography in order to determine the correlation of the measurements. Prostate volumes were calculated using the ellipsoid formula. Data were further analyzed in subgroups according to prostate volumes smaller or larger than 50 mL, measured by suprapubic ultrasonography. Results: The mean prostate volume of the 100 patients, measured by suprapubic and transrectal ultrasonography were 65.9 Â± 35.8 mL and 62.5 Â± 32.0 mL, respectively (r = 0.94; P < .001). The craniocaudal diameters had the strongest correlation among dimension measurements (r = 0.89; P < .001). Suprapubic and transrectal ultrasonography measurements also showed significant correlations for both prostates smaller or larger than 50 mL. Eighty-five percent of the patients had both volume measurements under or above this limit. Conclusion: There was strong correlation between suprapubic and transrectal ultrasonography measurements of the prostate sizes, including both for volume or specific dimension measurements.